Web-Based Automated Assessment for School Examinations - Jepri Yandi; Yuntari Purbasari (The IJICS (International Journal of Informatics and Computer Science), 2026)
An Assessment is a fundamental component of the educational process, particularly in school examinations, as it reflects students’ academic achievement. However, traditional examination and assessment methods often face challenges such as inefficiency, high administrative workload, and the potential for human error. This study aims to develop a web-based automated online assessment system to support ICT-based school examinations. The system is designed to facilitate online examinations, perform automatic scoring for objective test items, and generate assessment reports in real time. The development process follows a systematic software development approach, including requirement analysis, system design, implementation, and system testing. Functional testing results show that the system operates correctly and provides accurate assessment results. The implementation of the proposed system enhances efficiency, accuracy, and transparency in the examination and assessment process. Therefore, this web-based automated assessment system can be utilized as an effective ICT solution to improve the management and evaluation of school examinations.